PERBEDAAN DERAJAT KECEMASAN WANITA PERIMENOPAUSE YANG MENGIKUTI YOGA DAN TIDAK MENGIKUTI YOGA - Erina Wahyuni; Vita M. T. Lubis; Tuti Wahmurti A. Sapiie (PAIFORI, 2020)
Anxiety is one of clinical manifestations of perimenopausal phase. Managing anxiety is important because excessive anxiety can lower the quality of life of perimenopausal woman. Beside pharmacological treatment, there are some nonpharmacological treatment options which can be used to manage excessive anxiety, one of them is by don yoga. The purpose of this research is to know the difference of anxiety level between perimenopausal women with and without yoga. This research is an analytical observation using cross-sectional method. Research subjects were selected randomly, consisted of 103 perimenopausal women between the ages of 39 – 51 which divided into 2 groups, namely perimenopausal women with and without yoga. Data was collected using a self-completion questionnaire and consist of general identity, information about participation in yoga, and Zung’s Self-Rating Anxiety Scale to measure the anxiety level. Result shows that on the group of perimenopausal women with yoga, 5 respondents (9,8%) are anxious and 46 respondents (90.2%) are not anxious. On the group of perimenopausal women without yoga, 16 respondents (30.8%) are anxious and 36 respondents (69.2%) are not anxious. Data analysis shows that there is significant difference in anxiety level between perimenopausal women with and without yoga (p=0.008). Conclusion of the study is the anxiety level of perimenopausal women with yoga is lower than the anxiety level of perimenopausal women without yoga.